2006
DOI: 10.1111/j.1467-8527.2006.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

The Zombie Stalking English Schools: Social Class and Educational Inequality

Abstract: The aim of this article is to reclaim social class as a central concern within education, not in the traditional sense as a dimension of educational stratification, but as a powerful and vital aspect of both learner and wider social identities. Drawing on historical and present evidence, a case is made that social inequalities arising from social class have never been adequately addressed within schooling. Recent qualitative research is used to indicate some of the ways in which class is lived in classrooms. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
206
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(221 citation statements)
references
References 24 publications
4
206
0
11
Order By: Relevance
“…While there are examples of productive participation, the pattern of collective trajectories of this group differs sharply from that of traditional entrants (Reay 2006). The onus falls largely to students to adapt to established practices which remain strongly oriented towards traditional white middle-class populations (Read et al 2003, Burke 2005).…”
Section: Profitable Portfolios: Capital That Counts In Higher Educationmentioning
confidence: 99%
“…While there are examples of productive participation, the pattern of collective trajectories of this group differs sharply from that of traditional entrants (Reay 2006). The onus falls largely to students to adapt to established practices which remain strongly oriented towards traditional white middle-class populations (Read et al 2003, Burke 2005).…”
Section: Profitable Portfolios: Capital That Counts In Higher Educationmentioning
confidence: 99%
“…For example, the link between lower academic achievement at A Level and lower socio-economic status is well documented (Reay, 2006;Ball, 2008). Not surprisingly, the Organisation for Economic Cooperation and Development's (OECD) report, Education at a Glance 2011: OECD indicators (2011), reveals that, in the UK, young people in affluent areas were five times more likely to go to (any) university than those in poorest areas.…”
Section: The Distribution Of Wp In Higher Educationmentioning
confidence: 99%
“…(2010, p. 23) However, student choice is not and never can be 'sovereign', as access to many universities is highly competitive; places are over-subscribed and entry is conditional on qualifications gained within a deeply unequal, often distorted school system, (Chitty, 2002;Ball, 2006). Countless studies, (Reay, 2006;Allen & Ainley, 2007;Ball, 2008), have shown that the poor are often the poorly educated. As such, they have no clout as educational consumers in a cut-throat knowledge economy where funding, already scarce, is being cut further.…”
Section: Higher Education's Academic Writing 'Crisis'mentioning
confidence: 99%
“…Whilst the word 'partnership' is often espoused, one side of the partnership, the school, has more influence than the other. (Reay, 2008;2006;Vincent, 1996; Vincent and Tomlinson, 1997; Westergård and Galloway, 2010).…”
Section: Introductionmentioning
confidence: 99%